BERBAHASA DENGAN SANTUN - Sukarsono Sukarsono (Jurnal Bahasa Lingua Scientia, 2011)
Social interaction, which is an embrio of all kinds of social activities in human social world, occurs when it meets two conditions, namely social contact and communication.Through social interaction, human being can either cooperate or make conflict. To foster a heathy social interaction, we need a way of communication that secure a harmonious relationship among us. To use languange politely is a guarantee to come to a better communication for a healthy interaction. Brown and Levinson (1978/1987) offer us a theoretical prescription on how we should communicate politely. Politeness is viewed as a form of behavior which is  selected, decided, and practiced strategically in order to mitigate face threatening act (FTA) in an utterance.